Four weeks of sprint interval training improves 5-km run performance - Denham, J.; Feros, S. A.; O'Brien, B. J. (The Journal of Strength and Conditioning Research, 2015)
Sprint interval training (SIT) rapidly improves cardiorespiratory fitness but demands less training time and volume than traditional endurance training. Although the health and fitness benefits caused by SIT have received considerable research focus, the effect of short-term SIT on 5-km run performance is unknown. Thirty healthy untrained participants (aged 18-25 years) were allocated to a control (n = 10) or a SIT (n = 20) group. Sprint interval training involved 3-8 sprints at maximal intensity, 3 times a week for 4 weeks. Sprints were progressed to 8 by the 12th session. All participants completed a 5-km time trial on a public running track and an incremental treadmill test in an exercise physiology laboratory to determine 5-km run performance and maximum oxygen uptake, respectively, before and after the 4-week intervention. Relative to the controls, sprint interval-trained participants improved 5-km run performance by 4.5% (p < 0.001), and this was accompanied by improvements in absolute and relative maximum oxygen uptake (4.9%, p = 0.04 and 4.5%, p = 0.045, respectively). Therefore, short-term SIT significantly improves 5-km run performance in untrained young men. We believe that SIT is a time-efficient means of improving cardiorespiratory fitness and 5-km endurance performance.